Afromexicanos: entre el discurso académico y el reconocimiento constitucional - Tenorio López, Ariadna N. (2024)
The constitutional recognition of Black people in Mexico took place through a lengthy process involving Black populations, authorities, activists, and the sometimes-contradictory efforts of Mexican and foreign scholars. This article analyzes how Mexican blackness is constructed in texts from the American academy, as it has had the greatest exposure and impact in global academic discourse. Specifically, it refers to works that Mexican anthropologists acknowledge as having significant influence in the field of Afro-Mexican studies. The purpose of this analysis is to demonstrate how these works originate from a hegemonic locus of enunciation that privileges a first-world experience, hindering the understanding of the Black Mexican experience.